(untitled) - Romer, David (Boston, Mass., 2006)
David Romer’s Advanced Macroeconomics, 3e is the standard text and the starting point for graduate macro courses and helps lay the groundwork for students to begin doing research in macroeconomics and monetary economics. A series of formal models are used to present and analyze important macroeconomic theories. The theories are supplemented by examples of relevant empirical work, which illustrate the ways that theories can be applied and tested. This well-respected and well-known text is unique in the marketplace
Phân tích Kinh tế vĩ mô,Kinh tế học,Kinh tế vĩ mô
Keywords: Macroeconomics,Kinh tế vĩ mô